2021
DOI: 10.1093/ehjacc/zuab103
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the GoodSAM volunteer first-responder app on survival to hospital discharge following out-of-hospital cardiac arrest

Abstract: Bystander cardiopulmonary resuscitation and defibrillation can double survival to hospital discharge in out-ofhospital cardiac arrest. Mobile phone applications, such as GoodSAM, alerting nearby volunteer first-responders about out-of-hospital cardiac arrest could potentially improve bystander cardiopulmonary resuscitation and defibrillation, leading to better patient outcomes. The aim of this study was to determine GoodSAM's effect on survival to hospital discharge following out-of-hospital cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Dispatching first responders to OHCA strengthens the chain of survival and increases the likelihood of good neurological outcome [ 18 , 19 , 36 ]. This study illustrates the impact of the pandemic on FR schemes and gives an overview over the corresponding measures taken to mitigate the risks for responders and patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispatching first responders to OHCA strengthens the chain of survival and increases the likelihood of good neurological outcome [ 18 , 19 , 36 ]. This study illustrates the impact of the pandemic on FR schemes and gives an overview over the corresponding measures taken to mitigate the risks for responders and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of all European countries have implemented-to some degree-FR schemes [16] and the number is growing fast. FR schemes are associated with increased survival [7,[17][18][19]. A European registry study indicates, that regions operating such systems have significantly higher OHCA survival rates than other European regions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Three studies compared activation versus no activation of citizen first responders activation [17,21,29], three studies compared before and after the implementation of a network of citizen first responders [30][31][32]. The remaining three studies compared OHCAs where citizen first responders were activated and at least one responded versus no one responded [28], OHCAs where citizen first responders arrived first with those where EMS arrived first [15], and OHCAs where CPR was initiated by citizen first responders with those with CPR initiated by EMS [12].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eight studies investigated the effect of dispatching first responders to OHCAs on rates of bystander-initiated CPR [15,17,21,28,29,[31][32][33]…”
Section: Effect Of First Responders' Activation On Bystanders' Interv...mentioning
confidence: 99%
“…An early evaluation in out of hospital cardiac arrests showed that early response using the GoodSAM app was associated with improved survival, though the number of responses to alerts was fairly low and the study was not powered to find differences in survival. 12 "In a survey of ambulance staff in the north of England, more than 50% felt 'burnt out', and 87% had some degree of depersonalisation (including detachment and reduced empathy) towards their work ... "…”
Section: Why It Mattersmentioning
confidence: 99%